2021
DOI: 10.1111/ene.14806
|View full text |Cite
|
Sign up to set email alerts
|

Large vessel cardioembolic stroke and embolic stroke of undetermined source share a common profile of matrix metalloproteinase‐9 level and susceptibility vessel sign length

Abstract: Background Embolic stroke of undetermined source (ESUS) accounts for up to 25% of ischemic strokes. Identification of biomarkers that could improve the prediction of stroke subtype and subsequently of stroke prevention still remains a major issue. Methods The HIBISCUS‐STROKE cohort includes ischemic stroke patients with large vessel occlusion treated with mechanical thrombectomy following admission magnetic resonance imaging. Presence and length of susceptibility vessel sign (SVS) were assessed by gradient‐rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
4
0
1
Order By: Relevance
“…Another prominent finding of our study was that patients with the LAA subtype had a longer SVS compared to those with CE subtype, aligning with the recent findings reported by Alhazmi et al ( 19 ). Moreover, a CT study found non-cardioembolic stroke to be associated with longer thrombus duration compared to stroke caused by CE ( 22 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another prominent finding of our study was that patients with the LAA subtype had a longer SVS compared to those with CE subtype, aligning with the recent findings reported by Alhazmi et al ( 19 ). Moreover, a CT study found non-cardioembolic stroke to be associated with longer thrombus duration compared to stroke caused by CE ( 22 ).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the activation of the fibrinolytic system and spontaneous recanalization of occluded intracranial arteries poststroke could also impact the presence of SVS during the subacute stage. Compared to other stroke subtypes, CE has the highest spontaneous recanalization rate, which ranges from 18.8% to 72% in the literature ( 19 - 21 ). This phenomenon may contribute to the lower presence of SVS in the CE subtype during the subacute stage.…”
Section: Discussionmentioning
confidence: 96%
“…In support of the accuracy of SVS for detection of cerebral insults, Alhazmi et al (19) found the SVS length can differentiate cardioembolic from large-artery atherosclerosis subtype of embolic stroke of undetermined source with sensitivity and specificity rates of 79.7% and 72.7%, respectively. Also, Guenego et al (20) reported that clot shape in SVS as determined on T2 * imaging in patients presenting with proximal middle cerebral occlusion can predict the success of reperfusion during mechanical thrombectomy.…”
Section: Discussionmentioning
confidence: 95%
“…A study showed that the growth differentiation factor-15 level is associated with the severity of cerebral damage and can be used as a prognostic marker for patients who underwent intraarterial thrombectomy following an ischemic stroke (Jeong et al, 2020). Another study utilizing gradient echo T2*W imaging found that susceptibility vessel sign and admission MMP-9 levels can be used to differentiate between subtypes of stroke (Alhazmi et al, 2021). In a 3D MR vessel wall imaging study, type 2 diabetes mellitus was found to be associated with an increased number of intracranial plaques (Li et al, 2021).…”
Section: Integration Of Different Modalities and Future Directionsmentioning
confidence: 99%